2019
DOI: 10.1002/adma.201901103
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles of Ionic Liquids for Transdermal Drug Delivery

Abstract: Ionic liquids (ILs) and deep eutectic solvents have shown great promise in drug delivery applications. Choline‐based ILs, in particular choline and geranic acid (CAGE), have been used to enhance the transdermal delivery of several small and large molecules. However, detailed studies outlining the design principles of ILs for transdermal drug delivery are still lacking. Using two model drugs of differing hydrophilicities, acarbose and ruxolitinib and 16 ILs, the dependence of skin penetration on the chemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 53 publications
(65 reference statements)
2
115
0
1
Order By: Relevance
“…CAGE has been previously reported as an engineered ionic liquid/deep eutectic solvent that possesses excellent skin permeation, antimicrobial activity and the ability to enhance drug delivery into skin. 31,32 While extensive in vitro and in vivo assessment of CAGE has been reported in the literature, 22,33 its translation into preclinical development and clinical validation has not been reported. Furthermore, the higher concentration of choline in the skin and hence a higher molar ratio of choline:geranic acid (1.18) than that in the formulation (0.5) is likely due to the endogenous levels of choline.…”
Section: Discussionmentioning
confidence: 99%
“…CAGE has been previously reported as an engineered ionic liquid/deep eutectic solvent that possesses excellent skin permeation, antimicrobial activity and the ability to enhance drug delivery into skin. 31,32 While extensive in vitro and in vivo assessment of CAGE has been reported in the literature, 22,33 its translation into preclinical development and clinical validation has not been reported. Furthermore, the higher concentration of choline in the skin and hence a higher molar ratio of choline:geranic acid (1.18) than that in the formulation (0.5) is likely due to the endogenous levels of choline.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing those numbers is also a meter to highlight the level of details and knowledge in the field of “ILs and cells.” The comparison can finally be useful to guide the IL community to a set of new investigations, as well as stimulate the curiosity of the antibiotic and drug communities to further explore the impact of ILs in their fields. For example, it has been shown that ILs combined with antibiotics and drugs enhance their delivery across skin layers (Moniruzzaman et al 2010 ; Zakrewsky et al 2014 ; Tanner et al 2018 ; Hattori et al 2019 ; Tanner et al 2019 ; Qi and Mitragotri 2019 ). Furthermore, even though there are several studies on both cells and model biomembranes on the insertion of ILs, there are no investigations focusing on the effect of pH on IL-insertion, which can offer, however, a pathway to specificity and selectivity of ILs towards cancer cells, as shown for membrane peptides targeting tumors and other acidic tissues (Andreev et al 2007 ).…”
Section: Final Considerations and Remarks For The Futurementioning
confidence: 99%
“…Tunable ion stoichiometry and physicochemical properties are other key features of IL-based systems. Previous work in our group has indicated the role of interionic interactions in solvation and partitioning of the active ingredient into the skin (34). In addition, Chandran et al (35) have demonstrated the importance of electrostatic interactions and groove binding associations of ILs in DNA stability.…”
Section: Discussionmentioning
confidence: 87%